What value does blockchain bring to the imported fresh food supply chain?. (September 2022) - Liu, Shuai; Hua, Guowei; Kang, Yuxuan; Edwin Cheng, T.C.; Xu, Yadong
Highlights: Explore the impact of blockchain on the imported fresh food supply chain. Provide pricing strategies for the blockchain-based supply chain when blockchain is beneficial. Examine the value of blockchain in the sales of imported food. Discuss the impact of retailers' risk attitudes on blockchain-based fresh food supply chain. Abstract: During the COVID-19 pandemic, blockchain has been widely used to trace imported fresh food information from sources to destinations. Motivated by observations of real-world practice, we studied the role that blockchain played in imported fresh food supply chains. We first developed the basic models to examine the cases without and with blockchain. We derived the optimal pricing decisions for the supply chain and the conditions under which using blockchain was profitable under each model. To assess the robustness of the results, we then analyzed how risk attitudes affected the optimal supply chain decisions. We found some interesting results: When the effect of assuaging consumers' safety concerns brought by blockchain was not obvious, blockchain was more likely to help the manufacturer and retailer increase their profits; otherwise, the value of blockchain was not significant. Besides, the risk-averse manufacturer and retailer would decrease their prices in response to the risks of demand fluctuations. Also, the blockchain platform would benefit from the risk-averse manufacturer and retailer but suffer from risk-averse consumers.